Surface-pressure isotherms of monolayers formed by microsize and nanosize particles - Fainerman, V B; Kovalchuk, V I; Lucassen-Reynders, E H; Grigoriev, D O; Ferri, J K; Leser, M E; Michel, M; Miller, R; Möhwald, H (Langmuir, 2006)
The thermodynamic model of a 2D solution developed earlier for protein monolayers at liquid interfaces is generalized for monolayers composed of micro- and nanoparticles. Surface pressure isotherms of particle monolayers published in the literature for a wide range of particles sizes (between 75 microm and 7.5 nm) are described by the theoretical model with one modification. The calculations of surface pressure pi on area A provide satisfactory agreement with the experimental data. The theory also yields reasonable cross-sectional area values of the solvent molecule water in the range between 0.12 and 0.18 nm2, which is almost independent of particle size. Also, the area per particle in a closely packed monolayer obtained from the theory is quite realistic.